A comparative parallel design clinical study of Qurse Asabi in cases of post herpetic neuralgia (Indian Journal of Traditional Knowledge (IJTK), 2023)
In the case of established post herpetic neuralgia (PHN), the medication is simple analgesics, opioid derivatives (Tramadol), antidepressant (Amitriptyline), anticonvulsant (Carbamazepine), GABA agonist (Gabapentin & Pregabaline), etc., but the benefit of treatment does not outweigh its cost and hazards. Therefore, there is always an area of thrust that arises to find out a cost-effective and hazardless medication before expert of Physical medicine, Regimenist, Dermatologist, and general Physicians. As far as Unani Pharmacopeia is concerned there are several single and compound drugs indicated in ailment like wajaula’asab (neuralgia) but their efficacy in terms of documentation and validation is not established yet. A very important formulation prepared from Dawakhana Tibbiya College, Aligarh Muslim University Aligarh is usually indicated for neuralgic pain in routine practice. As far as PHN is concerned there is no medication indicated in classical literature. Therefore, this study was designed to find out the therapeutic efficacy of Qurse Asabi in comparison to most commonly prescribed allopathic medicines i.e., Neurokind-G containing Methyl Cobalamin 1500 mcg and Gabapentin 100 mg as a controlled drug while the Qurse Asabi is given as a test drug. The methodology was followed as per the Good Clinical Practice (GCP) guideline. Results were much interesting and encouraging which was also found statistically significant (t=10, p